Everyone must help: performance implications of CEO and top management team human capital and corporate political activity. Issue 2 (16th March 2021) - Harris, Christopher M.; Brown, Lee Warren
Abstract : Purpose: While research has shown that multiple actors, both internal and external to the organization, influence performance, oftentimes, these actors are studied in isolation. This paper aims to examine the performance implications of both top management team (TMT) and chief executive officer (CEO) human capital. In addition, the authors consider external actors' influence on performance by examining corporate political activity (CPA). Design/methodology/approach: The authors use a sample of National Collegiate Athletic Association (NCAA) football teams, examining human capital data on the head coaches and the assistant coaches, combined with the schools' participation in NCAA football committees. Findings: The study findings indicate that organizations engage in various market and nonmarket strategies in concert, and that different strategies result in performance outcome differences. Specifically, we examine how the use of CEO and TMT human capital and CPA interact and influence performance. Practical implications: The authors examine the moderating effects of political activity on the human capital–performance relationship for both top leaders and TMTs. Organizations benefit from investing in the human capital of their leaders internally and CPA externally. Originality/value: While organizations engage in market and nonmarket actions in concert, management research has generally studied these concepts in isolation. This paper suggests that both market and nonmarket activities can influence performance.